O14 Pilot of an independent domestic and sexual violence advocate (IDSVA) integrated within a central London sexual health (SH) and HIV service during COVID-19: 15 months of data. (16th June 2022) - Bennett, Amy; Tippetts, Darren; McCarthy, Sarah; Ashby, Jane; Ross, Roisin; Nur, Marian
Abstract : Introduction: During the COVID-19 pandemic and lockdowns, large increases in domestic abuse (DA) were reported 1 . A pilot project to evaluate the utility of a dedicated sexual health IDSVA was undertaken in a larger inner-city SH/HIV service. Methods: Commissioners were approached with data highlighting high numbers of high-risk DA identified within SH. Funding to pilot an integrated Sexual health IDSVA was obtained. The pilot ran between August 2020 - November 2021. Referrals were made to the IDSVA by clinic staff who identified DA victim/survivors during routine enquiry. Results: 121 referrals were received, of which 118 were accepted and 82% risk-assessed. Majority were cis-female (80%), heterosexual (81%) and aged 25-34yrs (37%). Five patients were aged under 18. 40% were for DA, 28% for SA, 22% for both DA/SA. 32% were assessed as high risk of harm. 44% was from ex-partner and 14% acquaintances. 21 cases involved child safeguarding considerations. IDSVA roles included face-to-face and telephone assessments, safety planning, arranging refuge, social care/safeguarding referrals, signposting and training/support for SH staff. Discussion: Significant numbers of patients with complex safeguarding needs, at high risk of harm were identified within sexual health, engaged with, and were supported by the SH IDSVA. Patient acceptability was reflected by the high uptake of IDSVA support (88%). IDSVA expertise and support freed up clinic staff time and resources. Funding has been agreed to expand this project further to an IDSVA team. Positive feedback from service users and staff has demonstrated the importance of the IDSVA role within SH settings. Reference: https://www.ons.gov.uk/peoplepopulationandcommunity/crimeandjustice/articles/domesticabuseduringthecoronaviruscovid19pandemicenglandandwales/november2020